Implications of a VLBI Distance to the Double Pulsar J0737-3039A/B - Deller, A.; Bailes, M.; Tingay, Steven (The American Association for the Advancement of Science, 2009)
The double pulsar J0737-3039A/B is a unique system with which to test gravitational theories in the strong-field regime. However, the accuracy of such tests will be limited by knowledge of the distance and relative motion of the system. Here we present very long baseline interferometry(VLBI) observations which reveal that the distance to PSR J0737-3039A/B is 1150220-160 parsecs, more than double previous estimates, and confirm its low transverse velocity (~9 kilometers persecond). Combined with a decade of pulsar timing, these results will allow tests of gravitational radiation emission theories at the 0.01% uncertainty level, putting stringent constraints on theories that predict dipolar gravitational radiation. They also allow insight into the system's formation and the source of its high-energy emission